The impact of tax restrictions on the structure of company financing sources - Biernacki, Krzysztof (Ograniczenia podatkowe a struktura źródeł finansowania przedsiębiorstwa, 2014)
Miller and Modigliani (MM) proved that the value of a firm is higher if the capital structure consist of equity and debt. The positive influence of the tax shield brings extra benefits for the company. This assumption may be modified by the thin capitalization rules, which excluded the interest paid to shareholders from the tax deductible costs. The article verifies the MM assumption in the Polish tax system, including the domestic regulation of thin capitalization. It has been shown that a loan from shareholders abroad may significantly influence the grounds for introducing such a regulation
Nauki o Finansach = Financial Sciences, 2014, Nr 4 (21), s. 83-91
Keywords: taxes; Miller and Modigliani theory; thin capitalization; opodatkowanie; teoria Millera i Modiglianiego; cienka kapitalizacja